KEBIJAKAN JUSTICE COLLABORATOR YANG BERKEADILAN - Gabriel, (2024)
Justice Collaborator is one of the instruments of Criminal Law used to reveal criminal acts committed jointly and organized. The enforcement of Justice Collaborator must fulfill the applicable laws and regulations. One of the phenomena in the enforcement of Justice Collaborator is Decision Number 798/Pid. B/2022/PN. Jkt.Sel which in the verdict gave Richard Eliezer as a Justice Collaborator in the crime of premeditated murder against Norfiansyah Yosua Hutabarat. This is the focus of research regarding the decision of the South Jakarta District Court Judge in accordance with the value of justice and the fair application of Justice Collaborators to the parties involved. The research conducted by the author uses normative juridical which includes library research. The author uses primary legal materials related to laws and regulations governing Justice Collaborators. The author also uses secondary and tertiary legal materials to support primary legal materials. Data collection techniques use library research and in analyzing data using descriptive analysis methods. In Decision Number 798/Pid. B/2022/PN. Jkt.Sel The judge in giving Justice Collaborator to Richard Eliezer is in accordance with the applicable laws and regulations and has fulfilled justice for the victims and perpetrators. In issuing a fair Justice Collaborator policy, law enforcement officials must fulfill the conditions stated in the applicable laws and regulations and there are still shortcomings regarding the application of the main perpetrator so that law makers must immediately fix it.